Comparison of Resilience and Subjective Well-being to Fathers and Mothers Who Have Postlingual Deafness Children - Destalya Anggrainy Mogot Pandin; Efi Fitriana; Aulia Iskandarsyah; Juke Siregar (Indonesian Institute for Counseling, Education and Therapy (IICET), 2019)
This study aims to compare the resilience and subjective well-being of fathers with mothers who have postlingual deafness children. Participants in this study were 336 parents (168 fathers and 168 mothers) who had postlingual deafness children, were biological fathers and mothers of postlingual deafness children, lived with their partners and children who experienced postlingual deafness, were able to communicate verbally and in writing using Indonesian good, domiciled in West Java. This research uses a comparative study approach. The instrument used in this study is the CD-RISC which has been modified into Indonesian by Lamsinar & Ratna (2011) and subjective well-being instruments constructed by researchers based on the Diener theory. The findings in this study reveal that there are significant differences in resilience and subjective well-being between fathers and mothers who have postlingual deafness children. Based on the average resilience and average subjective well-being seen in the group, the group of fathers who have postlingual deafness children has a higher score compared to the group of mothers who have postlingual deafness children.